The Use of Social Media Marketing on Marketing Performance with Digital Capability as a Mediating Variable in Service MSMEs - Purnamasari, Melan Susanty Purnamasari; Suwali, Suwali; Putranto, Afif Hendri Putranto; Syafi'ah, Syafi'ah; Handayani, Juli Handayani; Hasibuan, Reza Rahmadi Hasibuan (International journal of technology and education research, 2024)
This study aims to analyze the influence of social media marketing on marketing performance and digital capability in service-sector SMEs. The first hypothesis states that social media marketing has a positive impact on marketing performance. However, the results indicate that this hypothesis is not proven, with a P-Value of 0.245, which is greater than the alpha value of 0.05, making the relationship insignificant. The second hypothesis posits that social media marketing has a positive effect on SMEs’ digital capability, which is confirmed with a P-Value of 0.000 (less than alpha 0.05). The third hypothesis states that digital capability positively influences marketing performance, also proven with a P-Value of 0.000. These results suggest that although social media marketing does not directly improve marketing performance in service-sector SMEs, it enhances SMEs’ digital capabilities, which, in turn, positively impact marketing performance. The study implies the importance of developing digital skills in SMEs to enhance marketing effectiveness. This research also provides recommendations for further studies considering different SME sectors and other mediating factors in the relationship between social media marketing and marketing performance.